Local variations in the proportion of adult males in flocks of Goldeneye wintering in the Firth of Forth - Campbell, L H (Wildfowl, 1977)
Variation in the percentages of adult males in flocks of Goldeneye Bucephala clangula wintering between Cramond and Port Seton in 1975-1976 are described. Overall percentages at three sewer outfalls were: 70.8, 51.4 and 14.2, values at neighbouring locations falling within this range. In terms of both adult male percentages and flighting behaviour, there appeared to be three discrete groups present, the lowest percentage being in the area most sheltered from predominantly westerly winds. It is suggested that sex and age differences in local distribution reflect differences in tolerance towards factors such as shelter and disturbance, females and immature being more susceptible to differences in the degree of shelter.